Core/shell AgNWs@SnOx electrodes for high performance flexible indoor organic solar cells with >25% efficiency. (March 2023) - Xie, Chengcheng; Xiao, Chengyi; Fang, Jie; Zhao, Chaowei; Li, Weiwei
Abstract: In this work, an inorganic semiconductor SnO x has grown on the surface of silver nanowires (AgNWs) to form core/shell electrodes, which was successfully applied into flexible indoor organic solar cells (OSCs). Based on the redox reaction between Sn 2+ and Ag +, the pristine AgNWs thin films were treated by SnCl2 in an aqueous solution, so that SnO x was generated and meanwhile the defect on the surface of AgNWs (ex. Ag + and polyvinylpyrrolidone) was removed. SnO x can not only improve the stability, but also more importantly, tune the work function of AgNWs due to its n-type semiconducting nature. Therefore, photogenerated charges were efficiently injected and collected at the electrode. With this AgNWs@SnO x electrode, flexible indoor OSCs provided a high efficiency of 25.51% under 1000 lux illumination, while the unmodified AgNWs electrode only showed an efficiency of 18.84%. Graphical Abstract: A redox reaction was used to treat silver nanowires to generate core/shell structures with inorganic semiconductor SnO x as protecting layer, so that flexible indoor organic solar cells based on this electrode provided a high efficiency of 25.51 % under LED light. ga1 Highlights: A redox reaction between Sn 2+ and Ag + to address the roughness, conductivity and stability issues of AgNWs. Flexible OSCs based on AgNWs@SnO x provided champion efficiency of 25.51% under 1000 lux LED.